(untitled) (Medical Forum Monthly, 2021)
Objective: To find out the frequency of urinary tract infection in diabetic males. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Lady Reading Hospital Peshawar Medical A ward from December 2020 to May 2021. Materials and Methods: 150 patients were involved in study. These patients had type one and type two Diabetes mellitus and they did not take medicines for any illness. on microscopic examination of urine those patients who had >5 pus cells per high power field (phf) were selected and their mid stream urine (MSU) sample was than referred for culture and sensitivity. The culture results urine samples having colony forming units equal to 105/ml of urine were considered as positive. Results: 150 male diabetic patients comprising of (120 type 2 DM & 30 type1 DM) were included in study. Leukocyturia >5/hpf was found in 58/150 (38.66%) cases.in these 58 cases, cultures of urine whose results were positive was noted only in 36 (62.1%) patients. It was noted that frequency of urinary tract infection was 24% and the Ecoli was most common bacterium noted in 18 cultures of urine.In patients having type 2 diabetes mellitus, it was noted that Leukocyturia >5/hpf was present in 47/130 (43%) cases and in 29/47(61.7%) patients culture of urine was noted positive. Patients, Leukocyturia >5/hpf was present in 11/30 (36.66%) and positive urine culture was found in 7/11 (63.64%) cases in type 1DM Conclusion: It was found that in both Type 1 and type 2 diabetes mellitus urinary tract infection occurs commonly.